Masking neo-liberal development: Polanyi, rule of law and dis-embedding dynamics. Issue 3 (4th September 2017) - Findlay, Mark
Abstract : Purpose: Polanyi in his analysis of market dis-embedding suggests a drift in economic relations from the social to the fictitious. The purpose of this paper is to add two crucial components to the dis-embedding dynamic: rule of law discourse as a market force away from the social, and through suspension of imagination and of disbelief, the incongruous compatibility of actual and fictional markets that further works against embedding. Design/methodology/approach: Theory building through the application and testing of the Polanyian market dis-embedding analysis is a central concern for the paper. Through the example of foreign direct investment (FDI) and the manner in which the rule of law discourse masks neo-liberal development inequities, the paper offers an understanding of the forces behind market dis-embedding North to South Worlds and the manner in which through the collusion of legal orientalist, the true impact of the development inequities are concealed. Findings: The empirical value of the theorising is to allow for studies on the impact of FDI on fragmented South World market economies using Polanyian dis-embedding refined by the suspension of critique which the rule of law discourse enables. Originality/value: The masking functions of the rule of law discourse in global trade contexts, the paper argues, conceal stark market power asymmetries hardwired into South World development policy through post-colonial free-trade regimes. The legal certainty and commercial predictability that the institutions and processes of dispersed law are said to ensure, have an established market relationship with global trade. However, while resting on ideologies of liberty and equality, the rule of law discourse hides their market suspension in favour of stabilising and auctioning universally inequitable market conditions for the purposes of the neo-liberal global trade agenda.